PENDIDIKAN BERKELANJUTAN DALAM PENINGKATAN SDM DI DESA CIBODAS KECAMATAN RUMPIN KABUPATEN BOGOR - Rubyasih, Arina; Windyaningrum, Rachmawati; Koesanto, Stefani Made Ayu Artharini; Ekoresti, Stefani Nawati (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2024)
People can take education from everywhere, such as formal education conducted in schools. Additionally, there is non-formal education, which can occur outside formal education, such as in courses, training institutions, study groups, and others. Continuous education involves activities that aim to enhance evolving knowledge in one's job or responsibilities, leadership training, and improving managerial skills to manage institutions, finances, facilities, and human resources. This community service activity took place in Cibodas Village, Rumpin District, Bogor Regency/City, with the aim of raising awareness among the community about the importance of continuous education to improve human resource quality. The low level of education (above 75% at the elementary education level) is a social problem in the village. This training include materials about continuous education, entrepreneurship, and digital promotional media as a form of continous education. The training was provided to 50 participants from the Family Welfare Empowerment (PKK) of Cibodas Village, resulting in the creation of village flagship products. Through this training, participants will become catalysts, spreading information to raise awareness in the community and improve continuous education to achieve greater well-being and quality of life.